Amorphous calcium phosphate-containing orthodontic composites. Do they prevent demineralisation around orthodontic brackets? - Uysal Tancan; Amasyali Mihri; Koyuturk Alp Erdin; Ozcan Suat; Sagdic Deniz (Sciendo, 2023)
A preliminary study using laser fluorescence suggested that amorphous phosphate-containing orthodontic composites may prevent demineralisation around bonded orthodontic brackets.